Factors Related To Fatigue In Tofu Factory Workers In Mejing Candimulyo Village, Magelang - Choiril Salsabila Suada; Arianto, Machfudz Eko (Universitas Ahmad Dahlan, 2024)
Background: Fatigue is a condition in which the body physically and mentally shows differences that can result in decreased performance and lower body resistance to work activities. This fatigue condition can result in a decrease in work productivity and an increased risk of accidents. Some of the factors that cause work fatigue are age, working period and hot work climate. The existence of this study aims to determine the relationship between fatigue and age, working period and hot work climate in tofu factory workers in Mejing Village, Candimulyo District, Magelang. Method: this study is a quantitative research using a cross-sectional approach. A total of 31 respondents from tofu factory workers in Mejing Village, Candimulyo District, Magelang became research samples obtained by total sampling technique. Instruments used: Respondent data sheets, fatigue measurement table results and hot work climate measurement results. Data analysis using univariate and bivariate chi-square tests Result: The results showed that there was a gap between age and work fatigue (p-value 0.001), working period (p-value 0.006), and hot work climate (p-value 0.001) with the risk of work fatigue in tofu factory workers in Mejing Village, Candimulyo District, Magelang. Conclusion: there is a relationship between age, working period and hot work climate with work fatigue in tofu factory workers in Mejing Village, Candimulyo District, Magelang.